Binnenland ontmoet buitenland. De nasleep van onderzoekscommissies naar ontspoorde vredesmissies - Kemseke, Peter Van (BMGN - Low Countries Historical Review, 2010)
Klep, Christ, Somalië, Rwanda, Srebrenica. De nasleep van drie ontspoorde vredesmissies (Dissertatie Utrecht 2008; Amsterdam: Boom, 2008, 385 blz., ISBN 978 90 8506 668 2) When the Home Front meets Foreign Parts. The Aftermath of Commissions of Inquiry into derailed Peace Missions Peace Missions take place in difficult and volatile circumstances. It is therefore hardly surprising that some peace missions become ‘derailed’. Christ Klep zooms in on three ‘derailed’ missions in his book and focuses on the value of Commissions of Inquiry which are subsequently set up as a result of public and political pressure. Do they succeed in revealing the ‘how’ and the ‘why’ of such derailments and – above all – identifying those who are responsible? Based on a broad spectrum of questions and extensive source materials, Klep concludes that ‘the number of escape routes from the labyrinth of responsibility is practically infinite’; a clear message for all those taking part in international and domestic politics. It is here that the author skillfully and expertly succeeds: exposing the complex entanglement of domestic and foreign policy, even concerning events that sometimes happen away from the capital city. This review is part of the discussion forum ’Somalië, Rwanda, Srebrenica’ (Christ Klep).